PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN RETURN ON ASSET (ROA) TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BEI - FATIHITUL MIHRAD; M RIMAWAN; AMIRULMUKMININ AMIRULMUKMININ (GANEC SWARA, 2024)
Examining the impact of the Current Ratio is the goal of this associational investigation. This analysis makes use of secondary data derived from the financial records of the Cosmetics and Utilities Company Sub-Sector. A company's equity, debt, total assets, net profit, and current and non-current assets are all detailed in its financial statements. From 2018 to 2022, we surveyed residences using a purposive sampling strategy. Multiple linear regression, t-test, correlation coefficient, coefficient of determination, and classical assumptions were among the analytical procedures used to investigate the connection between X1 and SPSS v.26. The results show that X1 and X2 do not affect the value of the business as they are both more than 0.05. Rent On Asset (X3) values below 0.05 however have an effect on the value of the company